Understanding The Challenges Faced By Junior High School Students In Learning English Vocabulary From Listening Skill - N.Z Uyun; N. Authar; T. Saputri; Djuwari Djuwari; S. Zaniar (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
Listening skill is one of the most essential components in foreign language acquisition, particularly in supporting English vocabulary development among junior high school students. Through listening activities, students are expected to recognize pronunciation, understand word meaning, and connect spoken language with appropriate contexts. However, many students still experience difficulties in acquiring vocabulary through listening because spoken English often sounds different from its written form. This research aims to identify the main challenges faced by eighth-grade students in learning English vocabulary through listening skill. This study employed a qualitative case study design conducted at a junior high school in Surabaya. The data were collected through classroom observation, semi-structured interviews, and documentation. The participants involved eighth-grade students who had experienced listening-based vocabulary learning activities in English lessons. The data were analyzed descriptively by reducing, presenting, and interpreting the information obtained from the field. The findings show that students faced several challenges, including difficulty recognizing word pronunciation, inability to follow fast speech rates, limited vocabulary mastery, lack of contextual clues in audio materials, and low confidence during listening activities. Students also tended to depend on written texts and teacher explanations rather than using independent listening strategies. These problems affected their ability to understand new vocabulary from spoken input. The study suggests that teachers should apply more contextual and interactive listening activities, provide repeated exposure to audio materials, and use audio-visual technology to support students’ vocabulary learning. These strategies are expected to help students improve their listening comprehension and vocabulary acquisition more effectively.